Mata Kering pada Pasien Pascaoperasi Refraksi Mata Menggunakan Relex-Smile - Hana Qanitah; Himayani, Rani (Medula, 2024)
The eye is an organ that has many functions and is a vital organ in the body. The eyes have a part called photoreceptor which functions as light detector that will be stream to the retina of eyes according to its function. Based on data obtained from WHO, around 217 million people in the world have visual impairments. Refractive errors have several ways to correct them, one of which is using LASIK or with Refractive Lenticule Extraction, Small Incision Lenticule Extraction (RELEX SMILE). In a study conducted at the Eye Center Hospital, Hangzhou, Zhejiang Province, China in 2015, the incidence of dry eye complaints after RELEX SMILE surgery was 11% - 24%. A hospital in Semarang, reported that the incidence of dry eye complaints after RELEX SMILE surgery was 12%. This research is a Literature review which is a type of research that gathers theories that are relevant to the material that is currently researched, namely regarding dry eye syndrome. Researchers collected a number of articles from several databases like MEDLINE/PubMed, Google Scholar, and national also international journals. The result of the study found several complications in the procedure for healing eye refractive errors using RELEX SMILE, one of which is dry eyes. Dry eyes after RELEX SMILE and LASIK surgery is caused by damage to the sensory nerves in the cornea which may be caused by incisions during surgery. The incidence of dry eye after RELEX SMILE surgery can be prevented by a thorough examination by looking for signs and symptoms of dry eyes, or using drops without preservatives to reduce the impact of dry eyes.